PERAMPASAN TANAH DAN KONFLIK: KISAH PERLAWANAN SEDULUR SIKEP - Aprianto, Tri Chandra (BHUMI: Jurnal Agraria dan Pertanahan, 2018)
This paper draws how the people to make effort against land grabbing process in Kendeng montain range, Pati, Central Java. The conflict not only into make effort the struggle forms of violence, but also come into fights on ideas level, because the are other efforts to bear down the other to make academic and cultural in order to pave land grabbing. This paper gets to know a consciousness of people to make effort against land grabbing. The consciousness of the people is an expression of everyday live such as politic behavior, economic idea, and cultural idea. In addition resistant community, especially Sudulur Sikep speak against land grabbing at the basis on their belief, and one of their conection is the one with the land. Keywords: Land grabbing, industrialization, agrarian conflict, and Sedulur Sikep community.